2019
DOI: 10.1016/j.biomaterials.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular signals alter global gene expression profile of glioblastoma and response to temozolomide in a gelatin hydrogel

Abstract: Glioblastoma (GBM) is the most common primary malignant brain tumor, with patients exhibiting poor survival (median survival time: 15 months). Difficulties in treating GBM include not only the inability to resect the diffusively-invading tumor cells, but also therapeutic resistance. The perivascular niche (PVN) within the GBM tumor microenvironment contributes significantly to tumor cell invasion, cancer stem cell maintenance, and has been shown to protect tumor cells from radiation and chemotherapy. In this s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 86 publications
0
57
0
Order By: Relevance
“…Microglial cells have been associated with stimulating proliferation and invasion of GB cells, as well as mediating resistance towards cytotoxic drugs, such as vincristine and TMZ [165]. Co-culturing of GB cells with endothelial cells as well as stromal cells, which are important constituents of the perivascular niche of the tumour [166], led to upregulation of genes involved in angiogenesis, resulted in enhanced PI3K/Akt and Ras/MAPK signalling in GB cells and increased their resistance towards TMZ treatment [167]. In summary, primary data supports a resistance mediating role of the TME which is likely to contribute to a rather low five-year overall survival of less than 10% [168].…”
Section: Co-culture Systems Mimicking the Tmementioning
confidence: 99%
“…Microglial cells have been associated with stimulating proliferation and invasion of GB cells, as well as mediating resistance towards cytotoxic drugs, such as vincristine and TMZ [165]. Co-culturing of GB cells with endothelial cells as well as stromal cells, which are important constituents of the perivascular niche of the tumour [166], led to upregulation of genes involved in angiogenesis, resulted in enhanced PI3K/Akt and Ras/MAPK signalling in GB cells and increased their resistance towards TMZ treatment [167]. In summary, primary data supports a resistance mediating role of the TME which is likely to contribute to a rather low five-year overall survival of less than 10% [168].…”
Section: Co-culture Systems Mimicking the Tmementioning
confidence: 99%
“…Accumulating evidence has also demonstrated that EGFR and PAK1 participate in new capillary blood vessel formation and have a critical role in angiogenesis. For instance, upregulation of EGFR leads to poor survival through the activation of angiogenesis in glioblastoma ( 25 ). Effective inhibition of EGFR activation was indicated to ameliorate gastric tumor development through a delay in growth, induction of apoptosis, as well as inhibition of metastasis and angiogenesis ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate scaffold universality (i.e., whether they promote tissue formation), HCT116, CAFs, and TECs were co-cultured in parallel. Briefly, the three cell types were mixed at a ratio of 5:1:1 (depending on the histological features of the tumor tissues ( Figure S7 ) and the reference of tumor modeling 11 ), seeded onto sterile scaffolds then cultured in DMEM supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…To construct the 3D bio-printed tumor tissue (3DT), the collagen-PCL scaffold was placed in a petri dish (10 cm in diameter) and sterilized under UV light for 1 h. Activated stromal cells (CAFs and TECs) were mixed with tumor cells (HCT116) at a ratio of 5:1:1 (HCT116:CAF:TEC) and then seeded (1×10 6 cells/mL) onto the 3D scaffolds 11 . The scaffolds were placed in an incubator for 2-4 h with 2 mL DMEM to avoid uneven cell seeding caused by scaffold floating.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation